MUTU PELAYANAN KEPERAWATAN DI RUMAH SAKIT UMUM DAERAH RAJA TOMBOLOTUTU TINOMBO - Nuraliah (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
The quality of nursing services in Indonesia is still considered unsatisfactory, due to several reasons, such as nurses who do not pay enough attention to patients, nurses who do not provide enough care to patients, nurses who are less responsive in handling patient complaints. The aim of this research is to determine the quality of nursing services in terms of the dimensions of responsiveness, assurance, physical evidence, em-pathy and reliability at the Raja Kunciotutu Tinombo Regional General Hospital. This research uses descrip-tive research. The variable in this research is the quality of nursing services. The types of data are primary and secondary. Data collection uses a questionnaire. Data analysis uses univariate analysis. The population in this study were all patients who were treated in the inpatient room or who came for treatment at the Internal Poly-clinic. The sample in this study amounted to 97 respondents and the sampling technique used purposive sam-pling. The research results showed that 24 stated that responsiveness was good, 27 stated that responsiveness was sufficient, 46 stated that responsiveness was poor, 45 stated that the guarantee was good, 42 stated that the guarantee was sufficient, 10 stated that the guarantee was not enough, 7 stated that the physical evidence was good, 30 stated that the physical evidence was sufficient, 60 stated that the physical evidence poor, 5 said empa-thy was good, 18 said empathy was sufficient 4 said empathy was poor 31 said reliability was good 56 said reliability was sufficient 10 respondents said reliability was poor Conclusion based on the research results patients felt the quality of nursing services was still not good in terms of responsiveness, patients felt the quality of nursing services it is still not good from the physical evidence dimension and patients feel that the quality of nursing services is still not good from the empathy dimension. It is recommended that the Raja Kunciootutu Tinombo Regional Hospital make further efforts to improve the quality of nursing services by providing input to nurses who work in the inpatient ward and at the internal hospital .